A metal/UHMWPE/SiC multi-layered composite armor against ballistic impact of flat-nosed projectile. Issue 16 (15th August 2021) - Hu, Pengcheng; Cheng, Yuansheng; Zhang, Pan; Liu, Jun; Yang, Haifu; Chen, Jianyong
Abstract: A novel multi-layered composite armor system is proposed for ballistic protection in the present study. The composite armor is composed of a ductile metal front, followed by a ceramic/UHMWPE laminate composite as the intermediate layer, and a ductile metal back layer. The ballistic performance of the composite armor against flat-nosed projectile was investigated experimentally and numerically. Experimental results show that the proposed composite armor exhibited several failure modes, including ductile hole enlargement of metallic face sheets, fragmentations and cracks of the ceramic layer, delamination, fiber fracture and bulge deformation of UHMWPE laminates. Three-dimensional numerical model was established to analyze the evolution of the whole ballistic response, and to discuss the effect of the ceramic layer placement and the mass allocation between the ceramic layer and UHMWPE laminate layer on the ballistic performance. Simulation results reveal the evident reduction in residual velocity that results from the optimal placement of the ceramic layer. Good balance among the contributions of the target components can be achieved to maximize the total energy absorption of composite armor by optimizing the ceramic placement strategy. The projectile residual velocity and the total energy absorption are insensitive to the mass ratio of ceramic layer to UHMWPE laminate layer within a certain range. Under the condition of a higher mass ratio, the specific energy absorption of UHMWPE layer can be significantly improved due to the full development of its bulging deformation. Consequently, it would benefit the energy absorption capability of the composite armor.